The three dimensional microstructural network of elastin, collagen and cells in Achilles tendons - Pang, X.; Wu, J.; Allison, G.; Xu, J.; Rubenson, J.; Zheng, M.; Lloyd, D.; Gardiner, B.; Wang, A.; Kirk, Brett (John Wiley & Sons, Inc., 2016)
Similar to most biological tissues, the biomechanical and functional characteristics of the Achilles tendon are closely related to its composition and microstructure. It is commonly reported that type I collagen is the predominant component of tendons and is mainly responsible for the tissue's function. Although elastin has been found in varying proportions in other connective tissues, previous studies report that tendons contain very small quantities of elastin. However, the morphology of and the microstructural relationship among the elastic fibres, collagen and cells in tendon tissue have not been well examined. We hypothesize the elastic fibres, as another fibrillar component in the extracellular matrix, have a unique role in mechanical functions and microstructural arrangement in Achilles tendons. Using confocal and Second Harmonic Generation (SHG) imaging techniques, this study examined the 3-dimensional microstructure of the collagen, elastin and cells in the mid-portion of hydrated rabbit Achilles tendons. It has been shown that elastic fibres present a close connection with the tenocytes. The close relationship of the three components has been revealed as a distinct, integrated and complex microstructural network. Notably, a "spiral" structure within fibril bundles in Achilles tendons was observed in some samples in specialized regions. This study substantiates the hierarchical system of the spatial microstructure of tendon, including the mapping of collagen, elastin and tenocytes, with 3-dimensional confocal images.